A Histogram Comparison Approach for Assessing Hydrologic Regime Alteration. (27th January 2017) - Huang, F.; Li, F.; Zhang, N.; Chen, Q.; Qian, B.; Guo, L.; Xia, Z.
Abstract: The histogram comparison approach (HCA) is proposed to assess the alteration of hydrologic regimes, which are characterized by the hydrologic metrics, for example, the indicators of hydrologic alteration. The HCA method considers alterations within the whole range of the hydrologic regime and estimates the alteration degree by comparing the pre‐impact and post‐impact histograms. A key parameter of the HCA method is the similarity degree, which considers both the class‐by‐class and cross‐class information of histograms and reflects how many features of the pre‐impact histogram remain in the post‐impact histogram. The alteration degree is defined as the mathematical maximum similarity degree, that is, 100%, subtracted by the actual similarity degree in the HCA method. Comparing the HCA method to the existing range of variability approach and histogram matching approach through theoretical analysis and case studies, the HCA method can eliminate some limitations of the range of variability approach and histogram matching approach methods and can more accurately and effectively assess the hydrologic regime alteration. The Ob and Yangtze Rivers, which are located in different climatic zones, are used as case studies. Hydrologic regime alterations impacted by reservoirs with different regulation abilities (daily, seasonally and yearly) were assessed using the HCA method, the results of which verified its rationality and practicability. More sites with a wider range of flow variations will be examined in the future to assess the applicability of the HCA method. Copyright © 2017 John Wiley & Sons, Ltd.